Penggunaan Media Visual Berupa Powerpoint untuk Meningkatkan Hasil Belajar Siswa pada Pembelajaran Pendidikan Agama Islam di Kelas IV SD N 54/IV Danau Teluk Kota Jambi - Muhammad Apriansa; Saidah Saidah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to improve student learning outcomes using visual media in the form of power points in islamic religious education learning in class IV SD N 54/IV Danau Teluk Jambi City. This type of search is claccroom action research (PTK) which is carried out in 2 cycles with the stages of planning, observation, evalution, and reflection. The subjects of this study were grade IV students at SD N 54/IV Danau Teluk, Jambi City, totaling 20 students.while the object of this research is the use of visual media in the form of power points to improve student learning outcomes. The results of this study indicate that there is an increase instudent learning outcomes with a percentage of the average value of the student learning outcomes in the pree-cycle of 25%, cycle I of 50%, and cycle II of 95% with a very good learning outcome category. In addition, there are results of the percentage of succes of student observations in cycle I of 62% and in cycle II of 94% with very good categories and an increase in teacher activities in cycle I of 74% and cycle II of 97% with very good categories.